Immunopathology and Immunosenescence, the Immunological Key Words of Severe COVID-19. Is There a Role for Stem Cell Transplantation? - Ligotti, Mattia Emanuela; Pojero, Fanny; Accardi, Giulia; Aiello, Anna; Caruso, Calogero; Duro, Giovanni; Candore, Giuseppina (Frontiers in Cell and Developmental Biology, 2021)
The outcomes of Coronavirus disease-2019 (COVID-19) vary depending on the age, health status and sex of an individual, ranging from asymptomatic to lethal. From an immunologic viewpoint, the final severe lung damage observed in COVID-19 should be caused by cytokine storm, driven mainly by interleukin-6 and other proinflammatory cytokines. However, which immunopathogenic status precedes this “cytokine storm” and why male older population is more severely affected, are currently unanswered questions. The ageing of immune system, i.e. immunosenescence, closely associated with a low-grade inflammatory status called “inflammageing”, should play a key role. The remodelling of both innate and adaptive immune response observed with ageing can partly explain the age gradient in severity and mortality of COVID-19. This review discuss how ageing impacts the immune response to the virus, focusing on possible strategies to rejuvenate the immune system with stem cell-based therapies. Indeed, due to immunomodulatory and anti-inflammatory properties, multipotent mesenchymal stem cells (MSCs) are a worth-considering option against COVID-19 adverse outcomes.